Decompensation in Direct-Acting Antiviral Cured Hepatitis C Virus Compensated Patients With Clinically Significant Portal Hypertension: Too Rare to Warrant Universal Β-Blocker Therapy. (18th June 2021) - Tosetti, Giulia; Degasperi, Elisabetta; Farina, Elisa; D'Ambrosio, Roberta; Soffredini, Roberta; Borghi, Marta; La Mura, Vincenzo; Primignani, Massimo; Lampertico, Pietro
Abstract : Nonselective β-blockers improve decompensation-free survival in viremic hepatitis C virus compensated cirrhotic patients with clinically significant portal hypertension, but their protective role after sustained virological response by direct-acting antiviral (DAA) is undefined. We evaluated the incidence of decompensation in DAA-cured Child-A patients without high-risk varices. During the 49-month (12–60) follow-up, only one of 148 patients decompensated (ascites), with a 4-year cumulative risk of 1%, but decompensation was associated with hepatocellular carcinoma. The risk of decompensation in DAA cured hepatitis C virus compensated Child-A cirrhotic patients with clinically significant portal hypertension but without high-risk varices is negligible; thus, questioning the need for nonselective β-blocker treatment in this setting (see Visual abstract, Supplemental Digital Content, 1, http://links.lww.com/AJG/B861 ).